A proposed content in health instruction for grade six of the Philippine Normal College Laboratory school based on pupil health interests, needs and practices - Arboleda, Corazon (Regala) 1934- ([Quezon City s.n.], 1963)
This is a proposal on health instruction content based on the discovered interests, practices and needs of grade six pupils of the Philippine Normal College Laboratory School.
Thesis (M.Ed.)--University of the Philippines
Keywords: Health education -- Curricula